Diseño y construcción de una rueda hidráulica para el parque temático del CITE-UNL - Fernández Tene, Danny Israel (2024)
The degree project was focused on the design, construction, and commissioning of a water wheel for power generation. It began by formulating innovative design proposals, both for the water wheel and for its components that complement the generation system. The main objective of the project was to create a system that takes advantage of accessible hydraulic energy to generate electricity efficiently. The design phase involved the careful preparation of the components that make up the system, from the water wheel to the power transmission and speed multiplication devices. Each aspect was designed with an optimization, efficiency, and performance approach of the entire system as a whole, in addition, the project was made dismountable to allow for more detailed studies regarding its design, components, and operation. The construction of the project was carried out using accessible materials in the city, which allowed for cost reduction and better design proposals with materials available within the medium. However, for the main components such as the micro-generator and charge controller, it was decided to import them because the country still does not have this type of technology. Once the construction stage was completed, the field tests of the project were carried out. The results obtained in this phase allowed us to confirm the correct functionality and optimum performance of the design elaborated. The water wheel demonstrated its capacity to convert the energy of the supplied flow into constant electrical energy. Keywords: Energy renewable, hydraulic, mechanical, generation, water wheel, generator.